2004
DOI: 10.1162/089892904322984553
|View full text |Cite
|
Sign up to set email alerts
|

A Neurocomputational Model of Analogical Reasoning and its Breakdown in Frontotemporal Lobar Degeneration

Abstract: Abstract& Analogy is important for learning and discovery and is considered a core component of intelligence. We present a computational account of analogical reasoning that is compat-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
144
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 43 publications
12
144
1
4
Order By: Relevance
“…The second hypothesis of the study suggested that adolescents with conduct disorder compared with normal peers, showed significant deficit in fluid reasoning and it was in accordance with the findings of Morrison et al and Cho et al (22,23).…”
Section: Discussionsupporting
confidence: 87%
“…The second hypothesis of the study suggested that adolescents with conduct disorder compared with normal peers, showed significant deficit in fluid reasoning and it was in accordance with the findings of Morrison et al and Cho et al (22,23).…”
Section: Discussionsupporting
confidence: 87%
“…This same region has been implicated in working memory (for a review, see Fletcher & Henson, 2001), relational reasoning (Robin & Holyoak, 1995;Morrison et al, 2004;Waltz et al, 1999), and inhibitory control (Morrison et al, 2004;Shimamura, 2000). Accordingly, it is plausible that changes in the prefrontal cortex are responsible for the reasoning deficits observed in older people.…”
Section: Discussionmentioning
confidence: 96%
“…Klauer (1992Klauer ( , 2014 stated that all inductive tasks can be solved by means of systematic comparison processes, which involve finding similarities and/or differences between task attributes and/or relations among attributes. Inductive reasoning undoubtedly plays an important role in (classroom) learning processes as well as in transfer, as these often also require the ability to detect regularities in seemingly non-ordered material and rules for task solving (e.g., Csapó, 1997;Csapó, Molnár, & Nagy, 2014;Goswami, 1992;Klauer & Phye, 2008;Morrison et al, 2004;Perret, 2015;Vosniadou, 1989). Close inspection of children's inductive reasoning abilities, including the influence of training on the use of more advanced solving strategies (e.g., Higgins, 2015), is complex as a consequence of the variability in performance over time, as sketched above.…”
mentioning
confidence: 99%